Transfer Pricing: Strategies, Practices, and Tax Minimization - Klassen, Kenneth J.; Lisowsky, Petro; Mescall, Devan (Contemporary Accounting Research, 2017)
Abstract Using a survey of tax executives from multinational corporations, we document that some firms set their transfer pricing strategy to minimize tax payments, but more firms focus on tax compliance. We estimate that a firm focusing on minimizing taxes has a GAAP effective tax rate that is 6.6 percentage points lower and generates about $43 million more in tax savings, on average, than a firm focusing on tax compliance. Available COMPUSTAT data on sample firms confirm our survey‐based inferences. We also find that transfer pricing‐related tax savings are greater when higher foreign income, tax haven use, and R&D activities are combined with a tax minimization strategy. Finally, compliance‐focused firms report lower FIN 48 tax reserves than tax‐minimizing firms, consistent with the former group using less uncertain transfer pricing arrangements. Collectively, our study provides direct evidence that multinational firms have differing internal priorities for transfer pricing, and that these differences are strongly related to the taxes reported by these firms.